EMERGING PHOTOVOLTAIC TECHNOLOGIES photophysics and devices. - Ponseca, Carlito S. ([S.l.] : PAN STANFORD PUBLISHING, 2019)
The need to address the energy problem and formulate a lasting solution to tame climate change has never been so urgent. The rise of various renewable energy sources, such as solar cell technologies, has given humanity a glimpse of hope that can delay the catastrophic effects of these problems after decades of neglect. This review volume provides in-depth discussion of the fundamental photophysical processes as well as the state-of-the-art device engineering of various emerging photovoltaic technologies, including organic (fullerene, non-fullerene, and ternary), dye-sensitized (ruthenium, iron, and quantum dot), and hybrid metal-halide perovskite solar cells. The book is essential reading for graduate and postgraduate students involved in the photophysics and materials science of solar cell technologies.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Chemistry / Physical & Theoretical; SCIENCE / Life Sciences / General; TECHNOLOGY / Material Science; Photovoltaic power generation